Perlindungan HAM dalam Era Digital: Tantangan dan Solusi Hukum - Denda Ginanjar; Muhammad Fajar Firdausyi; Sobali Suswandy; Novita Tresna Andini (Journal on Education, 2022)
This article aims to provide a better understanding of how the challenges of the digital era can affect human rights and how the law can be used as a tool to protect these rights. In addition, this article also seeks legal solutions that can help maintain a balance between technological innovation and the protection of human rights. The text of this article was prepared using a literacy approach or literature review using various secondary library sources to answer all the problems in the research conducted. The results of the study regarding the challenges and legal solutions in protecting human rights in the digital era provide the conclusion that the challenges of protecting human rights in the digital era are very complex, but wise and effective legal solutions can help maintain a balance between technology and technology. innovation and individual rights. Implementing these solutions requires international cooperation, adaptation to technological developments, and awareness of individual rights in an ever-evolving digital world. By playing an active role in protecting human rights in the digital world, society has great potential to help create a digital environment that is safer, fairer and respects individual rights. In a world that is increasingly digitally connected, the role of society is very important in maintaining a balance between technological development and protecting human rights.